Industry Effects of Bank Lending in Germany - I. Arnold; Clemens J. M. Kool; K. Raabe (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2011)
We investigate the industry dimension of bank lending and its role in the monetary transmission mechanism in Germany. We use dynamic panel methods to estimate bank lending functions for eight industries for the period 1992-2002. Our evidence shows that bank lending growth predominantly depends on the industry composition of bank loan portfolios, both through the underlying cyclical fluctuations in industry-specific bank credit demand and through industry-specific credit supply effects.
Keywords: 330; Monetary policy transmission; credit channel; industry structure; dynamic panel data